Manajemen Ekstrakurikuler Di Sekolah Menengah Kejuruan (SMK) Terpadu Al-Ishlahiyah Singosari Malang - Iqlimah Maghfiroh (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
This study used qualitative descriptive method. The data were collected by means of observation, interview, and documentation. This study aims at describing the management of extracurricular activities in SMK Terpadu Al-Ishlahiyah Singosari. Extracurricular activities are performed outside the lesson haours that must be developed properly by a school, so that interest talent, and potential learners an be more optimally. In order to extracurricular activities an be run effectively then in the implementation required management functions of planning, organizing, actuating, and evaluation of extracurricular activities. The result achieved of implementation activities extracurricular in SMK Terpadu Al-Ishlahiyah is the active participation of students and development of talent learners in both academic and non academic.